Determinação da altura de voo de escolitídeos em mata nativa e em povoamento de Pinus taeda - Machado, Leonardo Mortari (2013)
Scolytids (Curculionidae, Scolytinae) are small borer‟s beetles belonging to the order Coleoptera that develop within or under the bark of trees. In northern countries, these insects cause significant damage especially when outbreaks occur. In Brazil in general, the damage is minor when compared to the northern hemisphere. Given the importance of subfamily Scolytinae, this paper aims at providing a better understanding of the behavior of Scolytids, mainly regarding the flight height in native forest and in a stand of Pinus taeda. For the execution of this work 72 intercept flight traps (PET Santa Maria) were installed in two areas (native forest and stand of Pinus taeda) belonging to the State Foundation for Agricultural Research (FEPAGRO), located at the mouth of the hill district, in Santa Maria, Rio Grande do Sul. The traps were distributed in 12 treatments (different heights) with three repetitions each and according to the environment, with an interval of 30 meters between repetitions. The treatments correspond to heights of 0.5, 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5; 6.0 meters. It was possible to capture: Hypothenemus eruditus in greater abundance at a height of 0.5 meter flight in native forest and in the range of 1 to 1.5 meters in Pinus taeda; Xyleborus saxeseni between 2 and 2.5 meters in native forest with no preference in the colonization of Pinus taeda; Microcorthylus quadridens in native forest at 2 meters; Xylosandrus retusus with no preference in both areas; Xyleborus ferrugineus to 0.5 meters in both areas; Corthylus pharax 0.5 to 1 meter in native forest; Xyleborinus gracilis and Xyleborus affinis to 0.5 meters in native forest. Therefore, it was possible to conclude that the range between 0.5 and 1.5 meters is ideal to analyze qualitatively and quantitatively the scolytids present in native forest and in the colonization of Pinus taeda.